Influence of cattle feeding on the technological and sensory quality of artisanal organic ch - Córdova Márquez, Sandra Elizabeth (2025)
Cheese production is a complex process that involves a variety of factors influencing the quality and sensory characteristics of the final product. In this literature review article, the effects of cattle feeding on milk composition and quality, as well as on the sensory properties of cheese, were examined, with a focus on organic cheese production. The discussion addresses how the animals’ diet, including grazing on organic pastures and the type of forage, impacts the composition of fatty acids and other compounds present in milk, which in turn affects the flavor, aroma, and texture of cheese. In addition, the challenges associated with organic cheese production, such as food safety, quality management, and preservation issues, were considered. The importance of transparency in communication with consumers regarding production methods and safety protocols was highlighted. This article provides a comprehensive overview of the factors influencing cheese quality and suggests key areas for future research and development in the dairy industry.